If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + n = 33 Solving 20 + n = 33 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + n = 33 + -20 Combine like terms: 20 + -20 = 0 0 + n = 33 + -20 n = 33 + -20 Combine like terms: 33 + -20 = 13 n = 13 Simplifying n = 13
| 5a+5=5(a+1) | | 8y-2x=24 | | -2y+8x=24 | | 10(x-1)(2x+1)=0 | | 9x+2=4x-18 | | 9x+2=4x+18 | | 4x+13=9x-8 | | 24x+22x^2-30x^3= | | 44+44*3= | | x^3-x^2-30x= | | 6a(5a-6)=0 | | 5b^2-13b-6=0 | | 24+4y-4=0 | | 2=1+x | | -3mx=-y-2b | | 8a-12=12 | | 7y=2+3 | | 12m+9+7-1=20 | | 2b-3=16 | | a^2+b^2+c^2=d^2 | | 4x+1-5=12 | | x^2=3x+5 | | 12y-5=2 | | 4a+4=8 | | 3x^2+17x-6= | | 3x^2+17-6= | | 2X+35-15=20 | | 49-64x^2=0 | | 5n+25g=5.65 | | -7x-3y-2+7x= | | x+5y=57 | | x+5y= 57 |